2003
DOI: 10.5433/1679-0359.2003v24n1p63
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de aflatoxina e zearalenona em alimentos destinados ao gado leiteiro na Região Norte do Estado do Paraná

Abstract: ResumoOs fungos ocorrem em uma grande variedade de alimentos, inclusive nos volumosos e concentrados destinados à alimentação animal, e podem produzir micotoxinas sob certas condições. O presente trabalho teve por objetivo avaliar a presença das micotoxinas aflatoxina e zearalenona em alimentos fornecidos a bovinos de exploração leiteira na região Norte do Estado do Paraná, Brasil, utilizando como metodologia analítica a cromatografia em camada delgada. Das 272 amostras analisadas para aflatoxinas, 37 (13,6%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 8 publications
0
9
2
5
Order By: Relevance
“…They usually are ingredients very susceptible to contamination by mycotoxins and toxigenic fungi. Presence of mycotoxins in food for animal consumption was reported in different regions of Brazil (Sassahara et al, 2003;Gonçalez et al, 2004;Oliveira et al, 2008). A. flavus capable of producing CPA and aflatoxins were isolated from feed samples studied in this work (Silva et al, 2015).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…They usually are ingredients very susceptible to contamination by mycotoxins and toxigenic fungi. Presence of mycotoxins in food for animal consumption was reported in different regions of Brazil (Sassahara et al, 2003;Gonçalez et al, 2004;Oliveira et al, 2008). A. flavus capable of producing CPA and aflatoxins were isolated from feed samples studied in this work (Silva et al, 2015).…”
Section: Resultsmentioning
confidence: 81%
“…In all properties, the feeds are prepared using corn, cottonseed, soy beans and salt and they were stored in barrels, each of them with 20 kg capacity. Feed samples (500 g) were collected from nine different points of each barrel: three points at the upper third, three points at the medium third, and three points at the lower third (Sassahara et al, 2003). The samples were homogenized and stored in plastic containers, and sent to the laboratory for analysis of mycotoxins (aflatoxins and cyclopiazonic acid) and water activity.…”
Section: Samplesmentioning
confidence: 99%
“…According to SMITH & MOSS (1985), feed with good microbiological quality should present a maximum of 10 5 colony-forming units g -1 (CFU g -1 ). The results showed that only 17% of the feed and 2.8% of forage samples had more than 10 5 CFU g -1 , therefore most of goat feeding had good quality in all farms studied.…”
Section: Resultsmentioning
confidence: 99%
“…In the properties, feed and forage were packed in barrels with a capacity of 20 kg each. Samples of the feed and forage were collected at nine different points of each barrel: three points of the upper third, three points of the middle third and three points of the lower third (SASSAHARA et al, 2003). Each sample contained a minimum of 500 g. The collected material was homogenized and stored in plastic packaging and sent to the laboratory for isolation and identification of the mycoflora and water activity analysis.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation